A method review of the climate change impact on crop yield - Feng, Xinyao; Tian, Haoliang; Cong, Jiahui; Zhao, Chuang (Frontiers in Forests and Global Change, 2023)
Climate change has a significant impact on global agricultural production, highlighting the need to conduct comprehensive investigations assessing its effects on agriculture and identifying viable adaptation strategies. A variety of research methods have been employed by scholars to investigate this issue, ranging from simple to complex and from single to ensemble approaches. However, the selection of the method can affect the accuracy of the results obtained. Hence, it is critical to review the various methods used in the past. This paper aims to review three methods used for investigating the response mechanism of crops to climate change, namely manipulated experiments, process-based crop models, and empirical statistical models. The advantages and disadvantages of each approach will be elaborated, alongside avenues for future improvements. Current challenges will also be discussed, and potential directions for future research will be proposed. The integration of these methods may facilitate a better understanding of the response mechanism of crop yield to climate change, providing more effective support for safeguarding global food security and advancing the field.